Statistical Indicators System of Industrial Production Structure and Dynamics in Russia - S. S. Shishulin (Мир новой экономики, 2018)
The availability of high-quality indicators system is a precondition for any statistical analysis. Statistical indicators system is a set of interrelated and mutually corresponded statistical indicators with a strictly ordered structure aimed at solving a particular statistical problem. There are a lot of different systems of economic and statistical indicators that allow to make quantitative and qualitative assessments of socio-economic processes and programs, but they are not sufficiently informative to conduct a full economic and statistical analysis. The author believes that the most high-quality and representative system is a combination of indicators of national accounts and operational business statistics. The resulting system consists of five blocks of indicators characterizing structure, dynamics, product demand, trends and promising of industrial production. The sources of the content information database are public databases and it is positively evaluated. Finally, the resulting statistical indicators system of industrial production in Russia should be full and sufficient both for high-quality and complete analysis of the domestic industry, and for review analysis of the industry of main trading partners, Russian industry mostly depends on.